2023
DOI: 10.1002/smm2.1178
|View full text |Cite
|
Sign up to set email alerts
|

Highly conductive fiber with design of dual conductive Ag/CB layers for ultrasensitive and wide‐range strain sensing

Abstract: Recently the ever‐increasing demand for wearable electronics has greatly triggered the development of flexible strain sensors. However, it is still challenging to simultaneously achieve high sensitivity, wide working range, and good wearability. Herein, we developed a highly stretchable fiber strain sensor based on wet‐spun porous polyurethane (PU) fiber, and especially a unique conductive network of dual silver (Ag)/carbon black (CB) layers is constructed. Under strain, the rapid crack propagation on the brit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In general, the linearity and durability of a superhydrophobic flexible strain sensor depends on the design of the sensing mechanism of the dual conductive layer, which can be improved by integrating hybrid sensing nanomaterials. [69] Han et al [70] applied a facile and controllable layer-by-layer spraycoating strategy to generate PDMS/CNT/CB dual conductive layers. This sensor exhibited high linearity (0.996 from 0% to 40%, 0.998 from 0% to 70%, and 0.992 from 0% to 90%, respectively), and the sensor's cyclic durability exceeded 30 000 cycles (Figure 4a).…”
Section: Linearitymentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the linearity and durability of a superhydrophobic flexible strain sensor depends on the design of the sensing mechanism of the dual conductive layer, which can be improved by integrating hybrid sensing nanomaterials. [69] Han et al [70] applied a facile and controllable layer-by-layer spraycoating strategy to generate PDMS/CNT/CB dual conductive layers. This sensor exhibited high linearity (0.996 from 0% to 40%, 0.998 from 0% to 70%, and 0.992 from 0% to 90%, respectively), and the sensor's cyclic durability exceeded 30 000 cycles (Figure 4a).…”
Section: Linearitymentioning
confidence: 99%
“…In general, the linearity and durability of a superhydrophobic flexible strain sensor depends on the design of the sensing mechanism of the dual conductive layer, which can be improved by integrating hybrid sensing nanomaterials. [ 69 ] Han et al. [ 70 ] applied a facile and controllable layer‐by‐layer spray‐coating strategy to generate PDMS/CNT/CB dual conductive layers.…”
Section: Design Parameters Of Superhydrophobic Flexible Strain Sensorsmentioning
confidence: 99%
“…In addition, conductive gel fibers (PEDOT: PSS, 149 38 000 S m −1 ) (PEDOT/PANI, 150 200 S cm −1 ) (RGO-PEDOT:PSS-PVA, 101 114 S m −1 ) (PEDOT:PSS@PVA, 151 0.00163 S cm −1 ) (polyimide, 152 21 m S cm −1 ) (PAAS-PMA, 40 2 S m −1 ) (P(NAGA-co-AAm), 54 0.69 S m −1 ) (P(AAm-co-PAA)/Fe(III) 41 4.2 m S m −1 ) (lignin/core-cellulose nanofibrils [CNFs] 153 185.3 S cm −1 ) (IL@TPE, 154 ∼0.45 S m −1 ) (RCNFs, 155 0.07 S cm −1 ) (PEDOT:PSS/PEG, 156 50 S cm −1 ) (Ag/CB@PU, 157 5139.9 S m −1 ) having qualities of stretchability, improved conductivity, and consistency in electromechanical behavior are pivotal elements in the evergrowing realm of wearable technology. Here, Wu et al 158 reported a technique involving the shaping of a hydrogel reservoir into ultrathin and stretchable conductive fibers with remarkable self-healing and multi-responsive properties.…”
Section: Conductivitymentioning
confidence: 99%
“…In addition, surface decoration usually corresponds to a core-shell structure, and the stretchability can be maintained to a great degree. Ultrasonication induced interface sintering, 72 dip-coating, 73 ion adsorption and insitu reduction 74 are the most common preparation methods to construct conductive networks on the fiber surface. Niu et al 75 developed a 1D PU fiber composite with a dual conductive grid structure consisting of CNTs The sectional view of a core-shell silicone fiber with 2 wt% MWCNT.…”
Section: Surface Decorationmentioning
confidence: 99%